2020
DOI: 10.1108/afr-06-2020-0082
|View full text |Cite
|
Sign up to set email alerts
|

Does experience with agricultural loans improve farmers' well-being? Evidence from Benin

Abstract: PurposeThe purpose of this study is to examine the effect of loans provided by Benin's largest microlender.Design/methodology/approachA pipeline design and matching techniques contribute for identifying the causal effect. The loan treatment considered is loan experience. It includes program entry timing, take-up frequency and the amount obtained over six years. The study uses a cluster analysis to create comparison groups.FindingsExperience with agricultural loans has a statistically significantly positive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In their research, Seven and Tumen (2020) present evidence of international studies that support the positive relationship between agricultural credit and agricultural productivity and demonstrate using a combination of panel data that agricultural credit operates primarily on the agricultural component of GDP in developing countries and on agricultural labor productivity in developed countries. Agricultural loans have a statistically significant positive effect on beneficiaries' farm incomes, food security and women's empowerment (Sagbo and Kusunose, 2021). Sakhno et al (2019) agree with increasing the volume of external financing and achieving a close relationship between the parameters: Loan-investment-increase in production and sales to form a functional environment, considering the possibilities of optimizing financial costs.…”
Section: Agricultural Loans-a Literature Reviewmentioning
confidence: 89%
“…In their research, Seven and Tumen (2020) present evidence of international studies that support the positive relationship between agricultural credit and agricultural productivity and demonstrate using a combination of panel data that agricultural credit operates primarily on the agricultural component of GDP in developing countries and on agricultural labor productivity in developed countries. Agricultural loans have a statistically significant positive effect on beneficiaries' farm incomes, food security and women's empowerment (Sagbo and Kusunose, 2021). Sakhno et al (2019) agree with increasing the volume of external financing and achieving a close relationship between the parameters: Loan-investment-increase in production and sales to form a functional environment, considering the possibilities of optimizing financial costs.…”
Section: Agricultural Loans-a Literature Reviewmentioning
confidence: 89%
“…Seasoned farmers have upper hand in optimizing output [37] and knowledge regarding the application of inputs and effective mitigation of risks and other farming challenges [38].…”
Section: Repayment Status Of Loan Based On Experience In Farmingmentioning
confidence: 99%
“…With the improvement of farmers' living standards, they will pursue green production methods conducive to their own safety. The well-being and income level of farmers receiving credit support will be greatly improved (Sagbo and Kusunose , 2020). Money has a great in uence on people's life.…”
Section: Rural Nancial Institutionsmentioning
confidence: 99%
“…Scholars have done a lot of research on the impact of agricultural loans of rural nancial institutions on farmers' life and agricultural production. Khan et al (2007) found that agricultural loans have a positive impact on improving crop yield; Solomon et al (2016) showed that bank loans to farmers are conducive to improving farmers' living standards; Sagbo and Kusunose (2020) believed that in developing countries, services in the nancial sector provide favorable conditions for agricultural activities. Therefore, The conclusion that bank credit support has a positive impact on the development of agriculture has been con rmed by many scholars.…”
Section: Introducementioning
confidence: 99%